Determinants of voluntary online local budget transparency : a case study from Croatia - Ott, Katarina (Array, 2019)
This article analyses the determinants of the voluntary online local budget transparency (OLBT) of Croatian local governments. Budget transparency is one of preconditions for enabling citizens’ participation and improving public sector outcomes; however, the previous empirical results are ambiguous and inconclusive, with particular gaps for ex-socialist, fiscally centralized countries. To contribute to the existing literature, this article uses the principal-agent and legitimacy theories and non-linear panel data models for the 2015-2017 period to analyse 128 cities and 428 municipalities in Croatia. The findings show that local governments with higher residents’ per capita income, population, Internet access, and administrative and fi scal capacity voluntarily publish more budget documents online. Policy recommendations point to the urge for the reform of the country’s territorial and fi scal organisation, the promotion of budget transparency in less developed cities/ municipalities and for education of citizens about budgets. The main study limitation is the absence of a qualitative analysis of observed documents.